Barriers and drivers to the implementation of the "clean development mechanism" within the Nelson Mandela Bay Municipality: a case study - Wilson, Craig Michael (Rhodes University, Faculty of Commerce, Investec Business School, 2008)
The global threat of climate change is one of the most crucial environmental issues facing the world in modern times. In response to this threat, international governments have drafted the Kyoto Protocol which included the Clean Development Mechanism (CDM). The CDM is a scheme which invited developing countries, like South Africa, to become involved in climate change mitigation projects. While South Africa has been identified as an attractive host country for CDM projects, research has revealed that it lags behind other developing countries in this regard. This study provides a theoretical background to the CDM and grounds the subject within the field of Environmental Economics. Following a literature review of factors that could influence the involvement of a municipality in CDM projects, this thesis undertook a case study of the barriers and drivers to CDM implementation within the Nelson Mandela Bay Municipality (NMBM). Use was made of semi-structured interviews, where a questionnaire was used to guide the researcher's interview process. Five NMBM officers, who were likely to have been involved with CDM project implementation, were interviewed. Data collected was analyzed using a coding technique and was compared and contrasted to the literature in a process of explanation building. It was possible to elicit 14 factors that acted as CDM-barriers; seven that acted as CDM-drivers; and 10 that were required to change within the NMBM to encourage greater CDM involvement. Of the barriers, lack of awareness, poor political will and lack of funding emerged as the most inhibiting. Of the CDM-drivers, the potential financial benefits; ownership of infrastructure capable of producing carbon assets; and technology transfer emerged as the factors most likely to promote CDM involvement. With regards the factors that require change, it emerged that a positive response would result from a proactive stance by National Government on the CDM; the use of Public-Private-Partnerships to facilitate CDM projects; and improved communication and capacity building within the NMBM and the Nelson Mandela Bay business community. The main recommendation offered to the NMBM was for it to draft a Sustainable Development Policy as well as a formal sustainable development strategy to drive a coherent and consolidated approach to the Municipality's involvement with CDM projects. Further, it was proposed that the NMBM should, lobby National Government for it to promulgate enabling legislation and a framework which would encourage CDM investment in South Africa; and engage with local business to promote the active involvement of the Nelson Mandela Bay with the implementation of CDM projects. Keywords: Global Warming, Kyoto Protocol, Clean Development Mechanism, Sustainable Development, Environmental Economics, Public Sector, Nelson Mandela Bay Municipality.
Keywords: Nelson Mandela Metropolitan Municipality (Eastern Cape, South Africa); Local government -- South Africa -- Eastern Cape -- Case studies; Climatic changes -- South Africa -- Eastern Cape -- Case studies; Greenhouse gases -- Environmental aspects -- South Africa -- Eastern Cape -- Case studies; Environmental economics -- South Africa -- Eastern Cape -- Case studies; Greenhouse effect, Atmospheric; Global warming